The Influence of Liquidity, Profitability and Capital Intensity Toward Tax Avoidance in Mining Companies Listed on the Indonesia Stock Exchange - Louis Yosen Primsa Tarigan; Deva Aulia Ningrum Ubaidillah (Asian Journal of Applied Business and Management, 2023)
This research has the objective to analyze the influence of liquidity, profitability and capital intensity on tax avoidance practices. The research is conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021. Using the purposive sampling method, 19 companies were selected. Statistical tests conducted are descriptive test, classical assumption, multiple linear regression, and hypothesis test. All tests were performed by using SPSS version 26. This research shows that liquidity and capital intensity partially have an insignificant influence toward tax avoidance. Profitability partially has a significant influence toward tax avoidance. Furthermore, liquidity, profitability and capital intensity simultaneously have a significant influence toward tax avoidance.